Subacute toxicity test of Rhizophora apiculata bark extract on liver and pancreas histopathology of rats - Syazili Mustofa; Isnamurti Ciptaningrum; Caesaria Sinta Zuya (Acta Biochimica Indonesiana, 2020)
Background: Rhizophora apiculata, one of the mangrove plant widely spread in Indonesia, can be developed as a medicinal plant. The extract of the bark has been found to have antioxidant and anti-inflammatory. However, the toxicity of Rhizophora apiculata has not been established yet. Objective: This research aims to evaluate the toxicity of ethanolic extract of Rhizophora apiculata bark on histopathological changes in rat’s liver and pancreas. Methods: Subacute toxicity study of the ethanol extract of Rhizophora apiculata bark was performed in healthy male rats by administering the extract at doses of 57, 114, 228, 456, and 918 mg/kg of body weight daily for 28 days. The subacute toxicity in rats was determined by histological analyses. Results: No significant adverse effect of the extract at dose 57 mg/kg was found. However at and over 114 mg/kg dose of the extract exhibited toxicities to the rats’ liver. In addition, the toxic effect appeared in rats’ pancreas at and over 228 mg/kg dose. Conclusions: Rhizophora apiculata bark extract showed no toxicity at or below 57 mg/kg. The ethanol extract from bark of Rhizophora apiculata showed toxicity at 114 mg/kg by subchronic toxicity.